A planar chiral six-membered cyclic (amino)(ferrocenyl)carbene and its sulfur adduct. Issue 6 (15th June 2017) - Yasue, Risa; Miyauchi, Masaru; Yoshida, Kazuhiro
Graphical abstract: Abstract: A planar chiral ferrocene-fused cyclic aldimine was synthesized and a series of iminium salts were divergently prepared from it. The new carbene was generated from a salt by simple deprotonation with a strong base and identified by a carbene trapping experiment with sulfur. The sulfur adduct was fully characterized and its crystal structure implied that the new carbene would create an excellent chiral environment when used as a catalyst or a ligand in catalytic asymmetric synthesis. Abstract : ( Rp )-(−)-1-[(2 S, 4 S )-4-(Methoxymethyl)-1, 3-dioxan-2-yl]-2-[( E )-2-nitrovinyl]ferrocene: C18 H21 FeNO5 [ α ]D 23  = −696.0 ( c 0.001, CHCl3 ) Absolute configuration: ( R ) Source of chirality: all compounds (9, 10, 4, 5a-e, 11a, 12a): ( S )-(−)-1, 2, 4-butanetriol Abstract : ( Rp )-(−)-1-(2-Aminoethyl)-2-[(2 S, 4 S )-4-(methoxymethyl)-1, 3-dioxan-2-yl]ferrocene: C18 H25 FeNO3 [ α ]D 23  = −773.0 ( c 0.001, CHCl3 ) Absolute configuration: ( R ) Source of chirality: all compounds (9, 10, 4, 5a-e, 11a, 12a): ( S )-(−)-1, 2, 4-butanetriol Abstract : ( R )-(−)-3, 4-Dihydro-3 H -ferroco[ c ]pyridine: C13 H13 FeN [ α ]D 26  = −925.0 ( c 0.001, CHCl3 ) Absolute configuration: ( R ) Source of chirality: all compounds (9, 10, 4, 5a-e, 11a, 12a): ( S )-(−)-1, 2, 4-butanetriol Abstract : ( R )-(−)-2-Isopropyl-3, 4-dihydro-3 H -ferroco[ c ]pyridine-2-ium iodide: C16 H20 FeIN [ α ]D 26  = −925.0 ( c 0.001, CHCl3 ) Absolute configuration: ( R ) Source of chirality: all compounds (9, 10, 4, 5a-e, 11a, 12a): ( S )-(−)-1, 2, 4-butanetriol Abstract : ( R )-(+)-2-3-Pentyl-3, 4-dihydro-3 H -ferroco[ c ]pyridine-2-ium bromide: C18 H24 BrFeN [ α ]D 13  = +960.0 ( c 0.001, CHCl3 ) Absolute configuration: ( R ) Source of chirality: all compounds (9, 10, 4, 5a-e, 11a, 12a): ( S )-(−)-1, 2, 4-butanetriol Abstract : ( R )-(−)-2-Benzyl-3, 4-dihydro-3 H -ferroco[ c ]pyridine-2-ium bromide: C20 H20 BrFeN [ α ]D 26  = −448.0 ( c 0.001, CHCl3 ) Absolute configuration: ( R ) Source of chirality: all compounds (9, 10, 4, 5a-e, 11a, 12a): ( S )-(−)-1, 2, 4-butanetriol Abstract : ( R )-(+)-2-Benzydryl-3, 4-dihydro-3 H -ferroco[ c ]pyridine-2-ium bromide: C26 H24 BrFeN [ α ]D 20  = +640.0 ( c 0.001, CHCl3 ) Absolute configuration: ( R ) Source of chirality: all compounds (9, 10, 4, 5a-e, 11a, 12a): ( S )-(−)-1, 2, 4-butanetriol Abstract : ( R )-(+)-2-Mesityl-3, 4-dihydro-3 H -ferroco[ c ]pyridine-2-ium trifluoromethanesulfonate: C23 H24 F3 FeNO3 S [ α ]D 18  = +446.7 ( c 0.001, CHCl3 ) Absolute configuration: ( R ) Source of chirality: all compounds (9, 10, 4, 5a-e, 11a, 12a): ( S )-(−)-1, 2, 4-butanetriol Abstract : ( R, R )-(−)-2, 2′-(1, 2-Phenylenebis(methylene))bis(3, 4-dihydro-3 H -ferroco[ c ]pyridine-2-ium)dibromide: C34 H34 Br2 Fe2 N2 [ α ]D 27  = −720.5 ( c 0.001, CHCl3 ) Absolute configuration: ( R, R ) Source of chirality: all compounds (9, 10, 4, 5a-e, 11a, 12a): ( S )-(−)-1, 2, 4-butanetriol Abstract : ( R )-(+)-2-Isopropyl-2, 3, 4, 5-tetrahydro-1 H -ferroco[ c ]pyridine-1-thione: C16 H19 FeNS [ α ]D 24  = +192.2 ( c 0.01, CHCl3 ) Absolute configuration: ( R ) Source of chirality: all compounds (9, 10, 4, 5a-e, 11a, 12a): ( S )-(−)-1, 2, 4-butanetriol